Early detection of cell death using transmembrane water exchange magnetic resonance imaging - Kaika, Athanasia; Nagel, Luca; Höckendorf, Ulrike; Xie, Bangwen; Topping, Geoffrey J.; Schillmaier, Mathias; Beer, Irina; van Heijster, Frits H. A.; Rauch, Julian; Kuder, Tristan Anselm; Sühnel, Sandra; Erber, Bernd; et al. (Advanced science, 2025)
Cell death plays a key role in cancer progression and treatment. After its onset, cell membrane integrity is often compromised. Here, it is shown in cells, animals and humans that the transmembrane water exchange rate, measured using magnetic resonance filter-exchange spectroscopy (FEXSY) or imaging (FEXI), and quantified by the apparent exchange rate (AXR), is an early biomarker of cell death. AXR measurements detect the onset of cell death in vivo earlier than diffusion-weighted MRI (DWI) and in vitro with similar sensitivity as flow cytometry. 13C magnetic resonance imaging (MRI) measurements of the malate/fumarate ratio (MFR), following injection of hyperpolarized [1,4-13C2]fumarate, in tumors displaying diffuse necrosis, are correlated with AXR. AXR detects early treatment response in colorectal and lymphoma tumor models while the apparent diffusion coefficient (ADC) measured by DWI remains unchanged. AXR measurements in human uterine fibroids show sensitivity to post-treatment changes soon after embolization, demonstrating clinical translatability of the method.
Zuerst veröffentlicht: 17. Dezember 2025
Gesehen am 18.02.2026